Optimizing telemedicine for providing obstetric and reproductive health care services during COVID-19 pandemic - Sharmila, Vijayan; Babu, Thirunavukkarasu Arun; Balakrishnan, Padmapriya (International Journal Of Community Medicine And Public Health, 2020)
The coronavirus disease (COVID-19) outbreak was first declared in China in December 2019, and WHO declared the outbreak as a pandemic on 11 March 2020. A fast-rising number of confirmed cases has been observed in countries across all continents over the past few months. This pandemic is forcing government of nations to take strict measures such as complete lockdown and curfews to ensure that citizens stay at home, as a measure to contain the spread of infection. Health sector is facing challenges such as high demand for doctors, limited resources of personal protective equipment and challenges in providing in-person consultation due to fear of spread of infection. Telemedicine is making positive contribution to healthcare during this pandemic, as it caters to health care of people in wide geographical area without risk of acquiring COVID-19. Telemedicine is defined as the provision of health care services by health care professionals, using technology to exchange information. A broad range of obstetric and reproductive health services can be offered via telemedicine. Telemedicine can help pregnant women to maintain high quality of care during this pandemic without compromising on the perinatal outcome. It allows for constant interaction between patient and doctor throughout pregnancy, thereby ensuring that the goals of antenatal care are fulfilled, while limiting unnecessary travel and time away from work and family. This article mainly concentrates on the essential obstetric and reproductive health care services that can be provided by telemedicine during COVID-19 pandemic.